Transcriptional activity and variation analysis of genes critical for long-chain fatty acid (C≥16) elongation and desaturation in Pekin ducks - Dandan Sun; Yongtong Liu; Xiaoqin Li; Mengqi Ge; Meiyi Zhu; Yuqin He; Zhuocheng Hou (Poultry Science)
To deepen our understanding of long-chain fatty acid carbon chain elongation and desaturation in ducks, this study systematically analyzed the transcriptional activities of key gene promoters, including ELOVLs, FADSs, and SCDs. Predictive modeling coupled with statistical analysis revealed a prevalence of binding motifs for transcription factors, particularly those associated with Sp1, NF-1, and C/EBPalpha. Moreover, variation analysis of resequencing data from both wild and domestic ducks, specifically mallards and Pekin ducks, informed targeted mutagenesis within the core promoter regions of ELOVL2, ELOVL5, and ELOVL6. Notably, mutations at positions -56 G>C in ELOVL2, -52 T>C in ELOVL5, and -513 T>C in ELOVL6 significantly diminished transcriptional activity. These findings substantially enhance our understanding of the molecular mechanisms regulating the biosynthesis of long-chain fatty acids in ducks and support future genetic selection initiatives aimed at developing Pekin duck breeds with enhanced nutritional value.